Overturning Roe v. Wade: What are the Implications for Perinatal Nurses?. Issue 6 (November 2022) - Rohan, Annie J.
Abstract : The Supreme Court's decision to overturn Roe v. Wade has far reaching implications for women's health in the United States. Being forced to continue pregnancy will likely have a negative effect on maternal morbidity and mortality including mental health. The practice implications for perinatal nurses are discussed.